Can Initial Torque Value Predict the Success of Orthodontic Mini-Screws? - Tolga Topcuoglu; Ali Altug Bicakci; Oral Sokucu; N. Eren Isman (Galenos Yayinevi, 2013)
Objective:To investigate the correlation between initial torque and removal torque of orthodontic mini-screws.Materials and Method:Sixty-four orthodontic mini-screws (measuring 1.5 × 4.4 mm, 1.6 × 4.7 mm, 1.7 × 5.5 mm, and 1.8 × 5.6 mm) were used. All mini-screws were inserted into the fibulas of 8 male rabbits. The initial torque values were immediately recorded using a digital torque gauge. For 2 months, 115 g force was applied to mini-screws inserted into the right fibula of the rabbits. The same procedure was followed for inserting the mini-screws into the left fibula of the rabbits but without applying any force. After 2 months, the removal torque values were recorded for all mini-screws. All statistical analyses were performed using SPSS version 14.0 for Windows. Spearman's correlation coefficient was used to analyze the relationships between initial and removal torque values.Results:Intragroup comparison of all brands of mini-screws showed similar features. There were no statistically significant differences between the initial torque values of all mini-screws (p > 0.05). The Spearman correlation coefficient showed that correlations between the initial and removal torque values were insignificant (p>0.05).Conclusion:The results of this study suggest that the initial torque value is not a reliable method for predicting the success of a mini-screw.